2007
DOI: 10.3892/or.18.6.1571
|View full text |Cite
|
Sign up to set email alerts
|

Relation between telomerase activity, hTERT and telomere length for intracranial tumours

Abstract: Abstract. Human linear chromosomes are capped by specialized DNA-protein structures called telomeres. The present study analysed the telomerase activity, hTERT protein and telomere length in meningiomas and gliomas in relation to their WHO grading. Fifty-three freshly dissected tumour biopsies were analysed for telomerase activity, hTERT protein expression and telomere length. Telomerase activity was examined in 41 of the 53 biopsies. Telomerase activity was detected in 3 of 35 (8.6%) screened meningiomas (1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…telomere shortening as an early event in carcinogenesis (34,37). However, our results are consistent with several previous studies in which longer telomeres have been associated with absence of metastases in OSCC (35), a low grade in intracranial tumors (38), higher overall survival in lung cancer patients (36), and a lower risk of death in patients with prostate tumors (39). Moreover, a lack of correlation between telomere length and clinicopathologic characteristics has also been found in breast (40), colorectal (41), and head and neck (42) tumors.…”
Section: Discussionsupporting
confidence: 71%
“…telomere shortening as an early event in carcinogenesis (34,37). However, our results are consistent with several previous studies in which longer telomeres have been associated with absence of metastases in OSCC (35), a low grade in intracranial tumors (38), higher overall survival in lung cancer patients (36), and a lower risk of death in patients with prostate tumors (39). Moreover, a lack of correlation between telomere length and clinicopathologic characteristics has also been found in breast (40), colorectal (41), and head and neck (42) tumors.…”
Section: Discussionsupporting
confidence: 71%
“…They found a mean length of 7.165 kb (SD = 1.724) in 34 benign meningioma tumors. The mean telomere length for the three atypical meningiomas was 5.269 kb (SD = 1.107) and 6.472 kb (SD = 4.668) for the two malignant meningiomas [36]. Also, in two low-grade astrocytoma tumors, one sample had mean telomere length of 14.310 kb, while the telomere length for another was 9.236 kb.…”
Section: Discussionmentioning
confidence: 94%
“…Also, in two low-grade astrocytoma tumors, one sample had mean telomere length of 14.310 kb, while the telomere length for another was 9.236 kb. In one anaplastic astrocytoma and 11 glioblastomas, the mean length of telomeres was 4.903 and 5.767 kb (SD = 2.042), respectively [36]. Finally, they concluded that telomere length cannot be used as a putative prognostic marker as a sole but should be linked with hTERT expression and telomerase activity [36].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lower expression level of various factors involved in telomerase activity should impair telomere regeneration at each Sphase (23). Moreover, the altered expression of telomere capping factors might disrupt the capping complex, facilitating telomere degradation and shortening independently of the telomerase status (24,25). This correlates with telomeric damage possibly already appeared in LSCC cells, which may be one of the reasons as to why shortened telomeres result in increased sensitivity to ionizing radiation exposure.…”
Section: Discussionmentioning
confidence: 99%